PRDM14 Is a Unique Epigenetic Regulator Stabilizing Transcriptional Networks for Pluripotency - Seki, Yoshiyuki (Frontiers in Cell and Developmental Biology, 2018)
PR-domain containing protein 14 (PRDM14) is a site-specific DNA-binding protein and is required for establishment of pluripotency in embryonic stem cells (ESCs) and primordial germ cells (PGCs) in mice. DNA methylation status is regulated by the balance between de novo methylation and passive/active demethylation, and global DNA hypomethylation is closely associated with cellular pluripotency and totipotency. PRDM14 ensures hypomethylation in mouse ESCs and PGCs through two distinct layers, transcriptional repression of the DNA methyltransferases Dnmt3a/b/l and active demethylation by recruitment of TET proteins. However, the function of PRDM14 remains unclear in other species including humans. Hence, here we focus on the unique characteristics of mouse PRDM14 in the epigenetic regulation of pluripotent cells and primordial germ cells. In addition, we discuss the expression regulation and function of PRDM14 in other species compared with those in mice.